Wellposedness of a Cauchy Problem Associated to Third Order Equation - Ayala, Yolanda Santiago (Transactions on Engineering and Computing Sciences, 2022)
In this article we prove that the Cauchy problem associated to third order equation in periodic Sobolev spaces is globally well posed. We do this in an intuitive way using Fourier theory and in a fine version using groups theory. Also, we study its generalization to n-th order equation.